Host specialisation and the disparate fate of Ceropales bipunctata (Hymenoptera: Pompilidae) in New Brunswick and Ontario, Canada. Issue 6 (7th September 2017) - Klymko, John; Buck, Matthias; Robinson, Sarah L.
Abstract: Ceropales bipunctata Say (Hymenoptera: Pompilidae) is a cleptoparasitic spider wasp that has declined significantly in parts of its range. New survey work has revealed that the species is common and widespread in dune habitat along the Gulf of Saint Lawrence in New Brunswick, Canada. Its host was determined as Anoplius cleora (Banks) (Hymenoptera: Pompilidae), with Arctosa littoralis (Hentz) (Araneae: Lycosidae) as prey, the first host record for this species. The relative abundance of C. bipunctata in coastal New Brunswick sharply contrasts with a decline in Ontario, Canada, where it was thought to be extirpated. Based on body size, habitat, and locality overlap we postulate that the primary host of C. bipunctata in Ontario and western Québec, Canada, is a different species, Anoplius aethiops (Cresson), with A. atrox (Dahlbom) as a likely secondary host in southwestern Ontario. Both species are closely related to A. cleora and have undergone a decline in eastern Canada. Based on these new findings, we reassess the conservation status of C. bipunctata in Canada.